The Influence of Body Image and Energy Intake on Nutritional Status in Adolescents at SMAN 1 Cirebon City, Indonesia - Kurniasih, Farah Gustin; Wahidin, Muhammad Duddy Satrianugraha; Fachrudin, Duddy (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: Adolescents are among the groups vulnerable to nutritional problems. These issues can arise due to restrictive diets, self-assessment (body image), lifestyle choices, energy intake, physical activity, and knowledge of balanced nutrition. According to the WHO (2018), the prevalence of overnutrition among adolescents aged 15–19 years has risen significantly from 4% to over 18%. The increase was observed in 18% of females and 19% of males. Aims: This research aims to examine the correlation between body image, energy intake, and nutritional status among adolescents at SMAN 1 in Cirebon City. Methods: A quantitative approach with a descriptive research design was employed in this study. The sampling technique used was purposive sampling. Primary data were collected through questionnaires, 24-hour food recall interviews, and measurements of body weight and height. Statistical analyses included univariate and multivariate analysis. Results: The findings indicate that most adolescents had a negative body image (60.1%), good energy intake (44.0%), and normal nutritional status (70.2%). Data analysis using the Ordinal Logistic Regression test revealed that body image significantly affects nutritional status (p < 0.001), and energy intake also significantly affects nutritional status (p < 0.001). Conclusion: This study concluded that body image and energy intake significantly influence the nutritional status of adolescents. Statistical analysis demonstrated that adolescents with a positive body image and good energy intake are more likely to have normal nutritional status. Received: 25 September 2024 | Reviewed: 16 October 2024 | Revised: 30 November 2024 | Accepted: 12 December 2024.